2018
DOI: 10.1021/acschembio.8b00116
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Recognition by a Colistin Resistance Enzyme from Moraxella catarrhalis

Abstract: Lipid A phosphoethanolamine (PEtN) transferases render bacteria resistant to the last resort antibiotic colistin. The recent discoveries of pathogenic bacteria harboring plasmid-borne PEtN transferase (mcr) genes have illustrated the serious potential for wide dissemination of these resistance elements. The origin of mcr-1 is traced to Moraxella species co-occupying environmental niches with Enterobacteriaceae. Here, we describe the crystal structure of the catalytic domain of the chromosomally encoded colisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…This structure demonstrated that a tyrosine residue in close proximity to the catalytic nucleophile threonine was involved in a polar contact with the electronegative phosphate group of pEtN (37). However, ICR Mc was reported to function as a homodimer, and the Tyr 338 residue forming the polar contact was buried at the dimer interface and belonged to the second molecule of the dimer, not the same polypeptide chain coordinating the Zn 2+ to which the pEtN was bound (37). Instead, the monomeric structure of BcsG and the positioning of Tyr 277 in our structure suggests this residue may form polar contacts with glucan hydroxyl groups during the latter step of catalysis in which EcBcsG transfers pEtN from Ser 278 to the C6 hydroxyl of cellulose.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…This structure demonstrated that a tyrosine residue in close proximity to the catalytic nucleophile threonine was involved in a polar contact with the electronegative phosphate group of pEtN (37). However, ICR Mc was reported to function as a homodimer, and the Tyr 338 residue forming the polar contact was buried at the dimer interface and belonged to the second molecule of the dimer, not the same polypeptide chain coordinating the Zn 2+ to which the pEtN was bound (37). Instead, the monomeric structure of BcsG and the positioning of Tyr 277 in our structure suggests this residue may form polar contacts with glucan hydroxyl groups during the latter step of catalysis in which EcBcsG transfers pEtN from Ser 278 to the C6 hydroxyl of cellulose.…”
Section: Resultsmentioning
confidence: 93%
“…Stogios and colleagues (37) reported the only structure to date of a pEtN transferase family member bound to pEtN, Moraxella catarrhalis ICR (ICR Mc ). This structure demonstrated that a tyrosine residue in close proximity to the catalytic nucleophile threonine was involved in a polar contact with the electronegative phosphate group of pEtN (37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein expression and purification was essentially done as previously described . Briefly, the gene encoding for AAC(3)‐Ia from Serratia marcescens strain SCH88050909 (AAL51023.1) was cloned into pET28a vector for expression with N‐terminal His 6 ‐tag and a thrombin protease cleavage site and expressed in E .…”
Section: Methodsmentioning
confidence: 99%
“…Protein expression and purification was essentially done as previously described. 15 Briefly, the gene encoding for AAC(3)-Ia from Serratia marcescens strain SCH88050909 (AAL51023.1) was cloned into pET28a vector for expression with N-terminal His 6 -tag and a thrombin protease cleavage site and expressed in E. coli BL21 CodonPlus(DE3)-RIL. Bacteria was lysed by sonication, soluble protein was purified first via affinity chromatography using Ni-NTA column and then further purified by gel filtration using a HiLoad 16/60 Superdex75 prep-grade column.…”
Section: Cloning Expression and Purificationmentioning
confidence: 99%